Physical properties of local upland rice kupang east nusa tenggara, indonesia - Dicky Frengky Hanas; Ite Morina Y Tnunay; Welsiliana Welsiliana; Florian Mayesti Prima R Makin; Lukas Pardosi; I Gede Arya Wiguna; Lidwina Felisima Tae (STKIP Persada Khatulistiwa Sintang, 2022)
Local upland rice (Oryza sativa L.) is a type of cereal crop that has the potential for dry land areas. Farmers in Kupang plant upland rice/local rice that has been consumed and used for generations and is considered by the surrounding community as part of their ancestral heritage. The materials used in this research were local upland rice varieties as a result of exploration. The varieties of six local upland rice of Kupang studied in this research had different rice characters in terms of its weight, volume, density and yield.'Aen Molo' has the highest weight per grain and per 1000 grains, namely 0.024 g and 24.95 g, also the highest volume of 1000 grains of rice is 30 ml, while 'Aen Lekes' has the lowest weight per grain and per 1000 grains, namely 0.020 g and 19.66 g and also the lowest volume of 1000 grains, namely 23 ml. The Iodine test results showed that the local rice of Kupang was classified in the regular or non-glutinous rice group. Meanwhile, Alkali test results show that the six samples of local upland rice have a high gelatinization temperature which indicates that local upland rice in Kupang Regency has high amylose content.